2022
DOI: 10.1021/acsinfecdis.2c00445
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Spectrum of Activity and Mechanism of Action of MGB-BP-3

Abstract: MGB-BP-3 is a potential first-in-class antibiotic, a Strathclyde Minor Groove Binder (S-MGB), that has successfully completed Phase IIa clinical trials for the treatment of Clostridioides difficile associated disease. Its precise mechanism of action and the origin of limited activity against Gram-negative pathogens are relatively unknown. Herein, treatment with MGB-BP-3 alone significantly inhibited the bacterial growth of the Gram-positive, but not Gram-negative, bacteria as expected. Synergy assays revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…MGB-BP-3 ( 16 ) was discovered at the University of Strathclyde (Glasgow, UK) and was inspired by the actinomycetes-derived minor groove binders, distamycin, netropsin and thiazotropsin [ 109 , 110 ]. In addition to activity against C. difficile , 16 has activity against a range of G+ve bacteria including S. aureus and Enterococcus faecalis but is not active against G-ve bacteria due to a lack of intracellular accumulation [ 111 ]. It was shown that two molecules of 16 bound to the minor groove of dsDNA, which then interfered with transcription, the supercoiling action of gyrase, and the relaxation and decatenation by topoisomerase IV enzymes in vitro [ 111 ].…”
Section: Compounds Undergoing Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…MGB-BP-3 ( 16 ) was discovered at the University of Strathclyde (Glasgow, UK) and was inspired by the actinomycetes-derived minor groove binders, distamycin, netropsin and thiazotropsin [ 109 , 110 ]. In addition to activity against C. difficile , 16 has activity against a range of G+ve bacteria including S. aureus and Enterococcus faecalis but is not active against G-ve bacteria due to a lack of intracellular accumulation [ 111 ]. It was shown that two molecules of 16 bound to the minor groove of dsDNA, which then interfered with transcription, the supercoiling action of gyrase, and the relaxation and decatenation by topoisomerase IV enzymes in vitro [ 111 ].…”
Section: Compounds Undergoing Clinical Evaluationmentioning
confidence: 99%
“…In addition to activity against C. difficile , 16 has activity against a range of G+ve bacteria including S. aureus and Enterococcus faecalis but is not active against G-ve bacteria due to a lack of intracellular accumulation [ 111 ]. It was shown that two molecules of 16 bound to the minor groove of dsDNA, which then interfered with transcription, the supercoiling action of gyrase, and the relaxation and decatenation by topoisomerase IV enzymes in vitro [ 111 ]. This is mechanistically distinct from fluoroquinolones that cause an increase in double strand breaks, as well as induce recA and lexA SOS responses.…”
Section: Compounds Undergoing Clinical Evaluationmentioning
confidence: 99%
“…In an efficacy model, S-MGB-363 was as active as the standard of care drug, posaconazole, in combating infection in a mouse model of invasive aspergillosis. 58 Through its fluorescent properties, it was possible to observe that S-MGB-363 associates with the fungal cell wall before transporting to the nucleus. Association at the cell membrane was not observed in a lung epithelial cell line (A549), nor was uptake, suggesting that entry into the target cell is a primary reason for the selectivity of S-MGB-363.…”
Section: Taking a Broader Viewmentioning
confidence: 99%
“…Experiments have shown that this is because MGB-BP-3 fails to accumulate in cells of Gram-negative bacteria because in most cases, it is removed by the action of efflux pumps. 58 However, if efflux is blocked by an inhibitor such as PAβN or a mutant lacking an efflux pump is tested, MGB-BP-3 becomes effective again. It is a challenge to incorporate such features into new S-MGBs molecules themselves.…”
Section: Taking a Broader Viewmentioning
confidence: 99%
“…Signicant advances in native mass spectrometry (MS) have enabled the high-resolution detection of protein complexes in their native state, enabling protein function elucidation. 18,19 Further, native MS is a powerful tool to investigate ligandprotein complexes, [20][21][22] ligand-DNA complexes, 23 and molecular glue protein complex stabilization. 24,25 In contrast to protein denaturing MS techniques, native MS preserves protein complexes from solution into the gas phase enabling the analyses of protein complexes in their native state.…”
Section: Introductionmentioning
confidence: 99%